Volume 6A: Turbomachinery 2013
DOI: 10.1115/gt2013-94425
|View full text |Cite
|
Sign up to set email alerts
|

Winglets for Improved Aerothermal Performance of High Pressure Turbines

Abstract: This paper investigates the design of winglet tips for unshrouded high pressure turbine rotors, considering aerodynamic and thermal performance simultaneously. A novel parameterization method has been developed to alter the tip geometry of a rotor blade. A design survey of un-cooled, flat-tipped winglets is performed using RANS calculations for a single rotor at engine representative operating conditions. Compared to a plain tip, large efficiency gains can be realized by employing an overhang ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 0 publications
1
26
0
Order By: Relevance
“…The two-dimensional streamline at the mid-gap plane is used to describe the flow behaviour near the endwall. The methods of analysis are based on the previous research by Coull et al 8 The analysis process of this section, by contrast, is simplified to validate a basic changing trend of losses under different cases. The cut plane A and cut plane B (two black lines shown in Figure 10 33.5 at the cut plane A and then gradually turns to the Z-aixs direction.…”
Section: Discussion Of Tip Leakagementioning
confidence: 99%
See 1 more Smart Citation
“…The two-dimensional streamline at the mid-gap plane is used to describe the flow behaviour near the endwall. The methods of analysis are based on the previous research by Coull et al 8 The analysis process of this section, by contrast, is simplified to validate a basic changing trend of losses under different cases. The cut plane A and cut plane B (two black lines shown in Figure 10 33.5 at the cut plane A and then gradually turns to the Z-aixs direction.…”
Section: Discussion Of Tip Leakagementioning
confidence: 99%
“…An investigation into a novel winglet gained a reduction of 45% in exchange rate at a relatively large gap. 7 Coull et al 8 investigated the effects of winglet tip on the aerodynamic and thermal performance in an unshrouded high-pressure rotor by RANS methods. The results showed that the overhang around the full perimeter of the blade tip greatly improved efficiency, and notably increased the overall heat load, and remarkable efficiency improvements could be obtained without increasing the overall heat transfer to the blade by adopting winglet tip on only the early suction surface.…”
Section: Introductionmentioning
confidence: 99%
“…where the leakage flow quantities (ṁ l , v l ) are extracted from the TGP cells and then radially integrated. In order to determine M m and v m , Coull [7] proposes to use the isentropic values derived from the suction surface pressures gauged at 90% span. A similar approach was adopted here with the difference that the static pressure distributions were sampled at 80% of the span.…”
Section: Cfd Methods and Data Processingmentioning
confidence: 99%
“…Efforts have therefore been made to develop advanced tip geometries for unshrouded blades, aiming to seal the tip gap and reduce the blade heat transfer [6]. A mid-way between the two approaches are the so-called winglets [7]. The design most commonly employed in the industry is a grooved tip (or squealer tip) shape, featuring a partial or full rim which acts as a labyrinth seal [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Shroudless high pressure (HP) turbine blades can have peak Mach numbers within the tip gap of 1.8 and, thus, supersonic effects cannot generally be ignored Zhang et al 2011;Moore et al 1989;Moore & Elward 1993). Supersonic effects tend to occur over the aft region of the tip where the blade loading is highest, although the extent of supersonic flow over the tip is strongly dependent on the tip geometry (Coull et al 2014;Zhang et al 2014). This area of the tip is important because the blade thickness in this region is small which means complex tip geometries are often not feasible and this zone is typically difficult to cool.…”
Section: Introductionmentioning
confidence: 99%